2021
DOI: 10.1007/s10758-021-09516-3
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Approach for Evaluating and Accrediting Digital Competence of Digital Profiles: A Case Study of Entrepreneurs and Remote Workers

Abstract: During the last decades, digital competence has become essential at workplace. Nowadays, it is difficult to find a job where no ICT skills are required. At the same time, there is a lack of ecosystems for adult reskilling in digital competence. Moreover, most of them do not use of a common language and terminology, decreasing the possibilities of being used by a wider public. In addition, the assessment of digital competence cannot be done using simple self-assessment tests, but more complex tools such as simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
0
11
0
7
Order By: Relevance
“…Another strength of our study was the methodology followed. The development was carried out in an iterative process, which included two cycles of testing and refinement, validating the content of the construct to be assessed and the design of the items, ensuring that the expected knowledge and skills are covered, the item formats selected are suitable for that aim, the usability of the items/tests is correct, e.g., the simulations include all the actions and different possible paths, and finally, the items are well written and easy to understand, which is a key factor in the development of an item bank of DC [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strength of our study was the methodology followed. The development was carried out in an iterative process, which included two cycles of testing and refinement, validating the content of the construct to be assessed and the design of the items, ensuring that the expected knowledge and skills are covered, the item formats selected are suitable for that aim, the usability of the items/tests is correct, e.g., the simulations include all the actions and different possible paths, and finally, the items are well written and easy to understand, which is a key factor in the development of an item bank of DC [86].…”
Section: Discussionmentioning
confidence: 99%
“…[83]. Therefore, we defined an initial solution based on key studies identified [24,86,87] and from other key studies identified in the literature review, such as [8,9,11,32]. Once the new design proposition was established, it was necessary to examine and improve it after the testing and analysis [83].…”
Section: Phase 2: Development Of Theoretical Framework Solutions Base...mentioning
confidence: 99%
“…With regard to the former, by obtaining a complete picture of the current digital technologies used by university faculty and students in their courses, universities will have the opportunity to make further recommendations and invest in research topics to address the digital divide. Regarding the latter, the use of digital technologies is inevitable in the era of Industry 4.0, and the digital competency of the future industrial workforce depends on the planned development (Bartolomé et al 2022 ). As a bridge between learning and employment, universities have the opportunity to prepare students for the job market of the future and to contribute to the development of a digital industrial environment when we can effectively understand the digital competencies offered in university courses (e.g., by examining the extent to which the use of digital technologies in curricula in various fields is key to meeting current industry needs).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Faculty members and students can be trained to use online applications interactively and develop a lesson plan with a reduced cognitive load to improve efficiency [40]. [139] suggest that the curriculum be organized so that students take an active role in online education. Besides, they indicate that the university administration should ensure that students' and lecturers' satisfaction in the online education organization is continuously monitored to accumulate statistical data in dynamics.…”
Section: Proposed Recommendations For E-learningmentioning
confidence: 99%